Penyuluhan Interaktif Literasi Keuangan Guna Mencegah Jebakan Pinjaman Online Ilegal - Rahmiyanti, Sev; Marheni, Marheni; Fahrunnisa, Vinny; Zakaria, Muchammad Ridwan; Mahardika, Cindhita; Maghfiroh, Siti (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This service activity aims to increase public awareness regarding the dangers of online loans (Pinjol) and good financial management literacy. The method of implementing this community service used interactive counseling techniques. The target was 17 students of Jenderal Soedirman University. This activity consisted of 4 (four) stages which included initial analysis of needs, preparation, coordination of implementation, and evaluation of activities in the form of distributing questionnaires which are analyzed descriptively. The results of this service showed that any increase in knowledge and skills in using financial service providers for online loans (Pinjol), is especially illegal. The participants had been able to plan, control, manage, and save finances well and were able to prioritize their respective needs. Meanwhile, regarding financial literacy, the participants already have good basic financial knowledge, were quite familiar with the ins and outs of savings and loans and the dangers of illegal online loans, and were quite knowledgeable about the importance of insurance and healthy investment.